Effect of Hydrogen Mass Flow Rate on Performance and Emission Characteristics of a Dual-Fuel LPG Gas Engine: Experimental and Numerical Analysis - Febrianto, Wigung Tri; Sudarmanta, Bambang (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Indonesia’s electricity sector remains heavily dependent on fossil fuels, with gas-based generation widely used for small- and medium-scale applications. Although liquefied petroleum gas (LPG) burns cleaner than coal and diesel, LPG-fueled engines still emit carbon-based pollutants. Hydrogen enrichment is a promising transitional strategy to improve combustion and reduce emissions without major engine modifications. This study evaluates the effect of hydrogen mass flow rate on the operational characteristics of an LPG gas engine operating in dual-fuel mode using combined experiments and numerical simulation. Experiments were performed on a single-cylinder, four-stroke LPG engine–generator operated at a constant 3000 rpm under steady-state electrical loads. Hydrogen was supplied at controlled mass flow rates while LPG remained the primary fuel. Performance parameters, air–fuel ratio, operating temperatures, and exhaust emissions were measured. In parallel, in-cylinder combustion was analyzed using ANSYS Forte, supported by a mesh sensitivity study to ensure numerical reliability. Hydrogen enrichment improved performance across the investigated load range, yielding maximum increases of 12.2% in shaft power, 17.2% in torque, and 8.2% in brake mean effective pressure. Specific fuel consumption decreased by up to 13.1%, while thermal efficiency increased by up to 13.5% compared with LPG-only operation. Hydrogen-enriched operation enabled leaner combustion at equivalent loads and reduced engine and lubricant temperatures by up to 12.2% and 8.3%, respectively. Emissions decreased, with maximum reductions of 8.2% in CO and 9.4% in HC. These outcomes indicate that hydrogen primarily functions as a combustion enhancer by accelerating flame propagation and promoting more complete oxidation, supporting LPG–hydrogen dual-fuel operation as a practical pathway toward lower-carbon distributed power generation.